2020
DOI: 10.1093/ehjcr/ytaa094
|View full text |Cite
|
Sign up to set email alerts
|

A case report of an iatrogenic coronary cameral fistula treated by retrograde percutaneous coronary intervention

Abstract: Background Acquired coronary cameral fistula is an extremely rare condition that involves an abnormal communication between a coronary artery and a cardiac chamber. It usually occurs after chest trauma or cardiovascular interventions, such as percutaneous coronary intervention (PCI) and is associated with various outcomes, ranging from a stable status to haemodynamic instability. Acquired coronary cameral fistula frequently arises from the right coronary artery and drains generally into the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
0
8
0
4
Order By: Relevance
“…The clinical manifestations of CAVF vary depending on the etiology of the fistula and the severity of left to right shunting; however, the majority of CAVF in adults are asymptomatic [1]. There have been prior published case reports of iatrogenic CAVF and CCF that developed following various coronary artery interventions (Table 1 [2,[6][7][8][9]). The more common causes of iatrogenic CAVF and CCF include coronary perforation during stenting and guidewire-induced trauma [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The clinical manifestations of CAVF vary depending on the etiology of the fistula and the severity of left to right shunting; however, the majority of CAVF in adults are asymptomatic [1]. There have been prior published case reports of iatrogenic CAVF and CCF that developed following various coronary artery interventions (Table 1 [2,[6][7][8][9]). The more common causes of iatrogenic CAVF and CCF include coronary perforation during stenting and guidewire-induced trauma [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…There have been prior published case reports of iatrogenic CAVF and CCF that developed following various coronary artery interventions (Table 1 [2,[6][7][8][9]). The more common causes of iatrogenic CAVF and CCF include coronary perforation during stenting and guidewire-induced trauma [6,8]. Ohayon et al reported the development of a LAD-toleft ventricle fistula following primary PCI for an anterior ST-elevation myocardial infarction [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, more than 500,000 PCI procedures are performed annually worldwide [ 4 ]. Although many stent implantation operations are carried out successfully every day, the occurrence of a rare but potentially fatal situation during PCI should always be kept in mind [ 5 ].…”
Section: Introductionmentioning
confidence: 99%